Acoustic Sources of Accent in Second Language Japanese Speech. (June 2019) - Idemaru, Kaori; Wei, Peipei; Gubbins, Lucy
This study reports an exploratory analysis of the acoustic characteristics of second language (L2) speech which give rise to the perception of a foreign accent. Japanese speech samples were collected from American English and Mandarin Chinese speakers ( n = 16 in each group) studying Japanese. The L2 participants and native speakers ( n = 10) provided speech samples modeling after six short sentences. Segmental (vowels and stops) and prosodic features (rhythm, tone, and fluency) were examined. Native Japanese listeners ( n = 10) rated the samples with regard to degrees of foreign accent. The analyses predicting accent ratings based on the acoustic measurements indicated that one of the prosodic features in particular, tone (defined as high and low patterns of pitch accent and intonation in this study), plays an important role in robustly predicting accent rating in L2 Japanese across the two first language (L1) backgrounds. These results were consistent with the prediction based on phonological and phonetic comparisons between Japanese and English, as well as Japanese and Mandarin Chinese. The results also revealed L1-specific predictors of perceived accent in Japanese. The findings of this study contribute to the growing literature that examines sources of perceived foreign accent.